1991
DOI: 10.1002/bit.260380114
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐catalyzed peptide synthesis using inverse substrates: The influence of reaction conditions on the trypsin acyl transfer efficiency

Abstract: Benzyloxycarbonyl-L-alanine p-guanidinophenyl ester behaves as a trypsin "inverse substrate," i.e., a cationic center is included in the leaving group instead of being in the acyl moiety. Using this substrate as an acyl donor, trypsin catalyzes the synthesis of peptide bonds that cannot be split by this enzyme. An optimal acyl transfer efficiency was achieved between pH 8 and 9 at 30 degrees C.The addition of as much as 50% cosolvent was shown to be of minor influence on the acyl transfer efficiency, whereas t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…acceptors (28,29) and later extended by further examples (30,31). Our own studies demonstrated that, in addition to single amino acid derivatives, the 4-guanidinophenyl ester functionality also mediates coupling of nonspecific acyl moieties derived from peptides (Table 2) (27).…”
Section: Substrate Mimetics For Arg-specific Proteasesmentioning
confidence: 87%
“…acceptors (28,29) and later extended by further examples (30,31). Our own studies demonstrated that, in addition to single amino acid derivatives, the 4-guanidinophenyl ester functionality also mediates coupling of nonspecific acyl moieties derived from peptides (Table 2) (27).…”
Section: Substrate Mimetics For Arg-specific Proteasesmentioning
confidence: 87%
“…The advantage of this methodology is that the 4-guanidinophenylester (OGp) functionality mediates the acceptance of non-specific amino acid moieties in the specificitydetermining S 1 position of Arg-specific proteases such as trypsin, thrombin and clostripain, as well as the Phe-specific protease α-chymotrypsin ( Fig. 9) [85][86][87][88][89][90]. The substrate mimetic concept has been shown to be a powerful strategy for the incorporation of sterically demanding C α,α -dialkyl amino acids into the P 1 position of peptides [91].…”
Section: Incorporation Of α-Fluoroalkyl Substituted Amino Acids Takinmentioning
confidence: 99%
“…However, the range of amino acids serving as substrates is narrow, productivities are lower, mainly because of the low activity and stability of proteases in nonconventional media, and no general protocols for synthesis have been developed as opposite to the case of SPPS [60,188]. The broad specificity of proteases restricts their application in peptide synthesis, since the peptide product that accumulates during the reaction can be attacked hydrolytically by the proteases simultaneously with the synthesis reaction [199]. The broad specificity of proteases restricts their application in peptide synthesis, since the peptide product that accumulates during the reaction can be attacked hydrolytically by the proteases simultaneously with the synthesis reaction [199].…”
Section: Enzymatic Synthesis Of Peptidesmentioning
confidence: 99%